Metastatic gestational choriocarcinoma in lung incidentally found by hemoptysis and confirmed by DNA genotyping, highly suggesting the index antecedent pregnancy of a girl - Shohei Matsuo; Emiko Tomita; Kenjiro Fukuhara; Shogo Kasuda; Koichi Suzuki; Yoshitane Tsukamoto (Elsevier, 2019)
We experienced a 46-year-old Japanese female with metastatic choriocarcinoma in lung found by hemoptysis. The Pathology findings of the surgical lung specimen showed multiple foci of peripheral clustering of trimorphic malignant trophoblasts with central hemorrhagic necrosis. Tumor cells were mostly immunoreactive for human chorionic gonadotropin (hCG). The pathological diagnosis of metastatic choriocarcinoma in lung was made. Rather high level of serum hCG was seen. Urine pregnancy test was also positive. In general, gestational choriocarcinomas are thought to have better prognoses than non-gestational ones. To investigate whether choriocarcinoma in our case is gestational or non-gestational, we compared short tandem repeat (STR) patterns between maternal non-neoplastic lung and lung tumor. The DNA genotypes of choriocarcinoma in our case included those of normal lung tissue as a proper subset, so the tumor was judged to be biparental/gestational. Furthermore, amelogenin showed only X chromosome type in both samples and no STR pattern from Y chromosome was seen in both samples, suggesting the antecedent pregnancy of girls/females in our patient. She had no past history of molar pregnancies or abortions. In fact, she has four children aged 5-17 years old, one 10-year-old girl and three boys. So genetic analyses identified that metastatic gestational choriocarcinoma in lung is arising in association with the antecedent pregnancy of a girl. After the surgical resection of the lung tumor, she has received several cycles of chemotherapy and serum hCG has gradually decreased within 70 days after the operation. She is now alive with no evidence of disease 8 months after the removal of the lung tumor. Keywords: Gestational choriocarcinoma, Human chorionic gonadotropin, Lung metastasis, Hemoptysis, Short tandem repeats, DNA genotyping